Peranan Sistem Doku Dalam Meningkatkan Motivasi Menabung Nasabah Pada PT. BPRS Lantabur. - Sholahuddin, Muhammad Arif; Fahrullah, (Universitas Negeri Surabaya, 2019)
Saving is an activity recommended by Islam, but the motivation to save the community to save at the bank is considered lacking. Doku system is a system from PT. BPRS Lantabur Tebuireng is carried out to motivate customers to save at the bank. This research uses descriptive qualitative method with the aim of knowing the role of the doku system in increasing the motivation to save customers at PT. BPRS Lantabur Tebuireng. The results of this study indicate that the role of the doku system in increasing customer saving motivation plays an important role. Customers claim the convenience offered by the doku system makes customers want to save. These facilities include customers no longer need to go to the bank office and queue up again to save at the bank, and there is no limit on the amount of deposits, regardless of the amount of money to save will be received by the doku system officer.